Statistical analysis with excel - Schmuller, Joseph (Hoboken, NJ : John Wiley & Sons Inc., 2022)
In Statistical Analysis with Excel For Dummies, fully updated for the 2021 version of Excel, you'll hit the ground running with straightforward techniques and practical guidance to unlock the power of statistics in Excel. Bypass unnecessary jargon and skip right to mastering formulas, functions, charts, probabilities, distributions, and correlations.
Introduction -- Part 1. Getting started with statistical analysis with excel: A marriage made in Heaven -- Part 2. Describing Data -- Part 3. Drawing Conclusions from data -- Part 4. Probability -- Part 5. The Part of tens -- Part 6. Appendices -- Index.
Includes index.
Keywords: MICROSOFT EXCEL